CONTENT AND SIGNIFICANCE OF THE CASH FLOW STATEMENT - Juraev Davlat Jonibekovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In the context of economic development, the proper and optimal management of enterprise activities is a rather complex process. In particular, the rational management of the flow of cash and cash equivalents ensures the continuity and sustainability of an enterprise’s operations. That is, the correct organization of cash accounting and its continuous analysis expands the financial capabilities of the enterprise. In recent years, one of the characteristic features of the development of market relations in the Republic of Uzbekistan has been the rapid growth of the financial market and all its sectors. In a market economy, it is not enough for management entities to simply have information. It is necessary to work with this information, draw correct conclusions, and use them to improve production efficiency. Among the sources of information used for the effective management of enterprise economic activities are data on the movement of cash and cash equivalents.